(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
Some auditors may think that the audit process ends with discovering misstatements and informing management about them, while the discovery of misstatements may be classified by some as the first step in the phase of separating these distortions, as the auditor should collect these misstatements, evaluate them and detail them into misstatements involving errors or misstatements involving fraud Then evaluating it to material or immaterial according to what was stated in the international auditing standards and directing management to amend the essential ones. The importance of this research lies in identifying the concept of distortions and their types, identifying the method of evaluating distortions into substantial and non-essential. Also, identifying the management procedures in light of the auditor’s assessments of the detected misstatements.This research reached a number of conclusions, the most important of which are the existence of fundamental distortions in the process of recognition and measurement of the government support received from the Ministry of Finance, as well as the existence of a fundamental distortion in the measurement process and the disclosure of the full production stock of flour and bran.This research was concluded with a number of recommendations, the most important of which is the need to re-measure and disclose the amounts of government support received by the company from the Ministry of Finance, and as the researchers mentioned in the practical aspect, as well as the need to re-measure the stock of the end of the period of full production of flour and bran in a way that guarantees the truth and fairness of the financial statements.